2021
DOI: 10.1111/jcpt.13430
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tranexamic acid in the treatment of adult melasma: An updated meta‐analysis of randomized controlled trials

Abstract: Melasma is a commonly acquired pigmentary disorder characterized by symmetric hyperpigmentation appearing as brown macules and patches on sun-exposed areas of the face and neck. The precise mechanism of melasma remains unknown; however, melasma is associated with some factors, such as genetic susceptibility, ultraviolet (UV) light exposure, pregnancy, sex hormones, contraceptive pills, cosmetics, phototoxic drugs and inflammatory processes. [1][2][3] Melasma significantly affects patients' appearance and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…31 Moreover, tranexamic acid (TA) has been proven to interrupt the interaction between melanocytes and keratinocytes; so, its combination with laser therapy may have an unexpected effect. 32 Therefore, we hypothesized that a combination of LQSNY and drugs might promote the efficacy of LQSNY treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Moreover, tranexamic acid (TA) has been proven to interrupt the interaction between melanocytes and keratinocytes; so, its combination with laser therapy may have an unexpected effect. 32 Therefore, we hypothesized that a combination of LQSNY and drugs might promote the efficacy of LQSNY treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Combined chemical stripping has been reported to enhance laser effects, as its deeper penetration depth causes more epidermal melanin shedding and avoids the adverse effects of multiple laser treatments 31 . Moreover, tranexamic acid (TA) has been proven to interrupt the interaction between melanocytes and keratinocytes; so, its combination with laser therapy may have an unexpected effect 32 . Therefore, we hypothesized that a combination of LQSNY and drugs might promote the efficacy of LQSNY treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of randomised controlled trials assessing the use of oral tranexamic acid for adult melasma showed significant efficacy and safety. 19 Physicians should educate themselves and the patient regarding dosage, side effects and precautions before prescribing oral tranexamic acid. Topical use has not been found to be entirely effective.…”
Section: Treatmentmentioning
confidence: 99%
“…Melasma is an acquired hyperpigmentary disorder emerging most commonly as symmetric patches and macules on the areas of face and neck exposed to sun. 1 In fact, melasma is considered a cosmetic disfigurement that can adversely influence the quality of life. 2 Melasma can differ in severity as there are differences in the intensity of pigmentation and area of involvement.…”
Section: Introductionmentioning
confidence: 99%